The Italian job (1969) [videorecording (DVD)] - Collinson, Peter, 1936-1980; Caine, Michael; Coward, Noel, 1899-1973; Hill, Benny, 1925-1992 (Widescreen DVD collection., 1992)
Fresh from prison, Charlie begins to work on a heist that will either set him up for life - or send him up forever. Charlie and his unruly lot of thieves take on the mob, the police and the gridlocked traffic of Turin to rob a heavily armed shipment of gold bullion.